Has the COVID-19 Pandemic Affected Breast Cancer Stage and Surgical Volume? - Kara, Halil; Arikan, Akif Enes; Dulgeroglu, Onur; Tutar, Burcin; Tokat, Fatma; Uras, Cihan (Frontiers in Surgery, 2022)
Background This study investigates the effects of COVID-19 on the breast cancer stage and the volume of breast cancer surgery in a specialized breast institute. Methods Data of 332 patients who were diagnosed and treated for breast cancer between December 2019 and November 2020 were evaluated retrospectively according to periods of pandemic. Results A significant decrease in the number of operations, especially upfront surgeries rather than surgeries after NCT, was detected in the early period of the COVID-19 pandemic. It was found that patients with complaints were mostly admitted during this period (p=0.024). No statistical significance was found for age, sex, side of the tumor, type of tumor, surgery to breast, and axilla. Following the early period of the pandemic, it was observed that patients with mostly luminal, early-stage, and less axillary nodal involvement (p<0.05) were admitted, and as a result, it was founded that upfront surgeries increased, although no change in TNM staging was observed. However, it did affect the decision of initial treatment. Thus, the number of upfront surgeries was significantly higher than the NCT group (p=0.027) following the early period. Conclusion Surgical volume is significantly affected in the early period of the COVID-19 pandemic. To overcome overload due to delayed surgeries related to pandemics, some hospitals should be spared for oncological treatments. Following the early period, mostly luminal type, early-stage patients were admitted, probably because of increased self-awareness and short wave duration, but the breast cancer stage was not affected.